The lightning thief - Riordan, Rick. (New York : Scholastic Inc., 2006)
"Percy Jackson is about to be kicked out of boarding school...again. And that's the least of his troubles. Lately, mythological monsters and the gods of Mount Olympus seem to be walking straight out of the pages of Percy's Greek mythology textbook and into his life. And worse, he's angered a few of them. Zeu's master lighting bolt has been stolen, and Percy is the prime suspect.."--back cover.
Originally published: New York : Hyperion Books for Children, c2005.
Keywords: Mythology, Greek -- Juvenile fiction; Friendship -- Fiction; Fathers and sons -- Fiction